Hospital nurses' management of agitation in older cognitively impaired patients: do they recognise pain-related agitation?. (6th July 2022) - Graham, Frederick; Beattie, Elizabeth; Fielding, Elaine
Abstract: Background: cognitively impaired hospital patients often experience agitation and aggression due to pain. Agitation complicates care, increasing the risk of adverse outcomes and patient-to-nurse violence. Managing agitation is challenging for nurses. Literature suggests they may rely on antipsychotics while missing other more appropriately targeted treatments. However, nurses' management of agitation remains unclear and under-researched. Objective: the aim of this study was to investigate hospital nurses' management of agitation in older cognitively impaired patients with pain. Design: this was a descriptive correlational study using virtual simulation. Setting and participants: a total of 274 registered medical and surgical nurses from 10 public hospitals in Queensland, Australia participated in the study. Methods: nurses undertook a virtual simulation requiring them to manage agitation in a patient with dementia and an injury. Nurses also completed a post-simulation questionnaire. Their simulation performances were correlated with demographics such as seniority, workplace, training, experience and gerontology-specific knowledge. Constructed from an original, validated vignette, the simulation included branching pathways, video scenarios and an avatar that could converse with participants. Results: thirteen nurses (4.7%) recognised and treated the virtual patient's agitation as pain-related. Most nurses (89%) gave antipsychotics of which 207 (78%) gave these first-line and 102 (38%) used them twice. Independent of other variables, nurses most likely to diagnose pain were dementia-unit nurses (OR = 8.7), surgical-unit nurses (OR = 7.3) and senior nurses (OR = 5). Conclusions: hospital nurses predominately managed agitation with antipsychotics, a decision that most made after undertaking inadequate patient assessments. This confirmed a common gap in practice that may lead to the missing of pain in the clinical care of agitated patients with dementia and/or delirium. Video Abstract: